2020
DOI: 10.3389/fbioe.2019.00416
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Nutrient Limitation Role on Improvement of Growth and Poly(3-Hydroxybutyrate) Accumulation by Burkholderia sacchari LMG 19450 From Xylose as the Sole Carbon Source

Abstract: Burkholderia sacchari LMG19450, a non-model organism and a promising microbial platform, was studied to determine nutrient limitation impact on poly(3-hydroxybutyrate) [P(3HB)] production and bacterial growth from xylose, a major hemicellulosic residue. Nitrogen and phosphorus limitations have been studied in a number of cases to enhance PHA accumulation, but not combining xylose and B. sacchari. Within this strategy, it was sought to understand how to control PHA production and even modulate monomer compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 62 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…This is why a high PHA production was observed at a 200-500 mg/L nitrogen concentration in our experiments. Apart from the nitrogen concentration, the phosphorus concentration and osmotic pressure of the culture solution might also affect the growth of cells and PHA production [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is why a high PHA production was observed at a 200-500 mg/L nitrogen concentration in our experiments. Apart from the nitrogen concentration, the phosphorus concentration and osmotic pressure of the culture solution might also affect the growth of cells and PHA production [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The use of nutrients limitation strategy could also be further investigated with other nutrients. The limitation of phosphorus in the medium has been demonstrated to be effective in enhancing PHAs production in C. necator DSM 545 ( Grousseau et al, 2014 ), while this improved the growth of Burkholderia sacchari LMG19450 on xylose ( Oliveira-Filho et al, 2020 ). Double nutrients limitation, e.g., nitrogen-oxygen limitation, might also be applicable as this has been shown to enhance PHAs production in Halomonas boliviensis ( Garcia-Torreiro et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Biomass growth ( Xr ) during the biopolymer accumulation phase in phosphate-limited fermentations has been observed before. Cultivations using Burkholderia sacchari and xylose as substrate showed an increase in biomass during the accumulation phase, even when phosphate was depleted in the cultivation medium [ 27 ]. The authors suggested the existence of polyphosphate reserves accumulated during the growth phase [ 27 ].…”
Section: Discussionmentioning
confidence: 99%